Enhancing TVET Students’ English Speaking Skills at Community College Using the Snake & Ladder Game - K., Gopal; W. B., Quah (Online Journal for TVET Practitioners, 2023)
The students in this community college’s Hospitality Course had several difficulties speaking English, including anxiety of making mistakes, fear of being laughed at by their friends, and a lack of understanding of the pronunciation and grammar that they used. This study aims to determine the students speaking skills by enhancing their motivation level and also to determine how students can communicate effectively when games are integrated in the lesson. This research was implemented with SPM leavers who are attending Hospitality Course in a community college. Hence snake and ladder game being used as a way out to develop students’ motivation in speaking English. When snake and ladder game is induced in the learning process, students will learn to speak spontaneously while playing the games and indirectly they will be able to motivate and train themselves in being a skillful speaker gradually. The researchers used pre-test and post-test, the researchers’ observation and interviews with a few students. When students participated in speaking tasks, particularly during games, they felt more liberated, free, and confident, according to the findings. They work together, support each other, and interact. Furthermore, when they had to perform in small groups, they were relaxed and joyful. Games have been and will always be an important part of learning a second or foreign language. Researchers have pointed out the importance of using snake and ladder game in the English learning process. This game is motivating and exciting experiences for students to develop the speaking skills.